PENERAPAN MEDIA PETA KONSEP TERHADAP HASIL BELAJAR SISWA SMA GERADUS ADII MERAUKE - Asmaningrum, Henie Poerwandar; Gelong, Marsel Aguansi; Werang, Basilius Redan (Jurnal Inovasi Pendidikan Kimia, 2018)
This research is a classroom action research that aims to improve the students' chemistry result of grade XI of SMA YPPGI GERADUS ADII Merauke on the subject of chemical bond through concept map media. The research was conducted at SMA YPPGI GERADUS ADII Merauke in the odd semester of the academic year 2016/2017. The sample in this research is 14 students of class XI. The research procedure consists of 4 stages: planning, implementation, observation, and reflection which is done by 2 cycles. Data analysis techniques are quantitative data (Percentage of Completed Learning) and qualitative data (Percentage of Teacher Skills, Student Activity, and Student Attitude).The results showed that the percentage of learning achievement on prasiklus is 00.00%, on cycle I is 35.71%, and on cycle II is 85.71%. Percentage of teacher skill in cycle I is 77,78% in good category and cycle II is 86,11% in very good category. Percentage of student activity in cycle I is 68,08% and cycle II is 76,56% both are in good category. Percentage of student attitudes in cycle I is 50.89% and in cycle II is 75.00%. In conclusion there is an increase in chemistry learning achievement through the concept map media on the subject matter of chemical bonds in grade XI SMA YPPGI GERADUS ADII MERAUKE.